Respuesta fitosíntesis-irradianza del nanoplancton de dos ecosistemas acuáticos urbanos - Cruz Muñoz, María del Rosario; Martínez Arroyo, María Amparo (Revista de Biología Tropical, 1999)
Four series of experiments on the phytoplankton smaller than 20llm (nannoplankton) were performed during 1997 in two urban aquatic ecosystems: Lake Chapultepec and Lake Xochimilco, in Mexico City. The goal was to learn the nannoplankton photosynthetic capacities by means of laboratory experiments where photosynIhesis- irradiance (P-I) curves were constructed using an integrated system with a polarographic electrode and light and temperature control. Experimental data were fitted to exponential models. The maximum photosynthesis rates (Pmax) ranged from 0.28 to 3.96 µmol 02 mg Chl a-1 h-1 in Chapultepec Lake and from 0.07 and 2. 99 µmol 02 mg Chl a-1 h-1 in Xochimilco Lake samples. The highest production in Chapultepec occurred in the rainy season while in Xochimilco it was in the dry season. Saturation irradiance (Ik) varied from 18 to 295 µEm-2 s-1. The highest photosynthesis rates occurred when some Cyanobacteria genera were dominant (Microcystis spp. and Oscillatoria spp. in both lakes and Merismopedia spp. and Anabaenopsis sp. for Xochimilco Lake). Biomass expressed as chlorophyll a concentration had its maximum values in the rainy season, 220.9 mg m-3 in Chapultepec and 136. 2 mg m-3 in Xochimilco.